1999
DOI: 10.1117/12.349767
|View full text |Cite
|
Sign up to set email alerts
|

<title>Fiber optic Bragg grating sensors embedded in GFRP rockbolts</title>

Abstract: Rockbolt anchors for tunnel or mine roofs are key elements during construction and operation. We report on the fabrication of glass fiber reinforced polymer (GFRP) rockbolts with embedded fiber optical Bragg grating sensors and their first field application in a test tunnel.Optical fibers and in-fiber Bragg grating sensors were embedded in GFRP rockbolts during a continuously ongoing pultrusion process on a industrial production machine. Depending on their outer diameter the rods equipped with fiber sensors se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Embedding the fiber optic sensors inside the composite materials is very effective in transferring strain and protecting the fragile optical fiber from mechanical damage. Frank et al fabricated GFRP rock bolts instrumented with FBG sensors by embedding the FBG sensors in the GFRP rock bolts during the pultrusion process [ 41 ]. The tensile tests indicated that the embedded FBG sensors were able to survive a high strain of 1.5%.…”
Section: Rock Bolt Monitoring Using Smart Sensorsmentioning
confidence: 99%
“…Embedding the fiber optic sensors inside the composite materials is very effective in transferring strain and protecting the fragile optical fiber from mechanical damage. Frank et al fabricated GFRP rock bolts instrumented with FBG sensors by embedding the FBG sensors in the GFRP rock bolts during the pultrusion process [ 41 ]. The tensile tests indicated that the embedded FBG sensors were able to survive a high strain of 1.5%.…”
Section: Rock Bolt Monitoring Using Smart Sensorsmentioning
confidence: 99%
“…Existing packaging methods include gluing FBG to the target and embedding with adhesives [22,23,24,25,26], packaging FBG in pipes or on plates [25,27,28,29,30], or encapsulating FBG into composites or layered structures [20,31,32,33,34]. For field geohazard monitoring, the installation works can be extremely tricky since the optical fibers can hardly be adhered on geomaterials.…”
Section: Development Of Fbg-based Geohazard Monitoring Systemsmentioning
confidence: 99%
“…A common practice is to adhere the sensors on- or embed them in-soil reinforcements, such as geogrids, soil nails and anti-slide piles. As early as 1999, the use of glass fiber–reinforced polymer (GFRP) rock bolts with integrated FBG sensors for strain monitoring in a Switzerland tunnel was reported by Frank et al of the Swiss Federal Laboratories for Materials Testing and Research [31]. Nellen et al successfully monitored strain and temperature fields of tunnels with FBG instrumented GFRP rock bolts [35].…”
Section: Development Of Fbg-based Geohazard Monitoring Systemsmentioning
confidence: 99%
“…Nellen et al [10] embedded FBG sensors in the GFRP rock bolts in order to conduct pultrusion. The tensile evaluations showed that the embedded FBG sensors were capable of withstanding a high strain of 1.5%.…”
Section: Introductionmentioning
confidence: 99%